Desenvolvimento de um sistema de SHM sem fio e com compensação automática de temperatura - Cortez Ledesma, Nicolás Eusebio [UNESP] (2015)
Structural health monitoring have attracted much research interest over the last few decades. With recent advances in wireless communication technology, wireless networks can potentially offer a low-cost alternative to traditional cable-based sensing systems. This work presents the design and implementation of a novel wireless structural health monitoring system based on a promising and simple method to detect damage in structures using the electromechanical impedance principle. The proposed system is a wireless low-power scalable sensor network composed of smart sensor nodes, a link node and a remote monitoring center (host node and server). The link node is used as the coordinator of a ZigBee network of multiple smart sensor nodes; and as a gateway to integrate ZigBee network with the remote monitoring center via a GSM/GPRS network and/or an HTTP server. The smart sensor node, based on microcontroller, is a portable core, standalone, which automatically compensates measurements with environment temperature variation, may control various sensors and operates in either local or remote mode. The identification of damage is performed by simply analyzing the variations of root mean square voltage of the response signals from piezoelectric transducers, such as PZT (Lead Zirconate Titanate) patches bonded to the structure, obtained for different frequencies of excitation signals in time domain, and it is not necessary to compute the electromechanical impedance. The temperature compensation is performed using the correlation coefficients to compute the effective frequency displacement value from the data signatures. Experiments were successfully performed on an aluminum structure and temperature varying from 0oC to 60oC; the results indicate that the proposed smart sensor node, which can be monitored from anywhere in the world and is able to detect damage in the initial stage, even in the presence of ...